Immunological study of lactate dehydrogenase from Streptococcus mutans and evidence of common antigenic domains with lactate dehydrogenases from lactic bacteria. - Sommer, P (1986)
Rabbit polyclonal antibodies directed against purified Streptococcus mutans L-(+)-lactate dehydrogenase reacted with the purified enzyme, giving a marked deviation of its kinetic parameters. The enzyme affinity for pyruvate or NADH decreased in the presence of antibody, the affinity for fructose 1,6-diphosphate (FDP) appeared to be slightly affected, and the cooperativity of the ligand binding was lowered. A partial protective effect was observed when the enzyme was preincubated with FDP prior to the antibody adjunction. An enzyme-linked immunosorbent assay allowed detection of a 30% decrease in enzyme-antibody fixation when FDP was added. The protective effect observed with FDP could be correlated with a conformational change induced by the activator. A decrease of antibody binding in the presence of FDP was also obtained with S. sanguis, Actinomyces viscosus, and Lactobacillus casei lactate dehydrogenases, which reflects a similar mechanism of activation among lactic bacteria. NADH did not offer any protection against antibody inhibition or fixation, and the coenzyme affinity decrease could be attributed to an indirect mechanism. On the contrary, pyruvate and the immunoglobulins apparently could compete for specific binding sites. A decrease of antibody binding was also obtained with three heterologous lactic bacterial lactate dehydrogenases, indicating a conservation of antigenic determinants implicated in the substrate binding.